The Role of Automation in Human Resources Management Functions: A Field Study on Government Agencies in the Kingdom of Saudi Arabia - Alangari, Noura; Alaldakheel, Haifa (The Arab Journal of Administration, 2023)
The study aims to identify the role that automation plays in human resource management and its functions, and to what extent is automation applied in human resources departments in government agencies in the Kingdom of Saudi Arabia, and the most prominent challenges and obstacles faced by human resources departments when using them, The researcher used the descriptive curriculum, and the questionnaire was distributed to the study population, which numbered (204), and (65) questionnaires were retrieved. The study concluded that the automation is applied in human resource departments in government agencies in the Kingdom of Saudi Arabia to a high degree. And the technologies used in organizations are not modern and do not fit with work requirements, and automation plays a major role in the functions of human resources departments, where the field of “planning” and the field of “recruitment / Acquisition “ came with the highest arithmetic average at a high degree, and the most prominent obstacles and challenges facing the automation activities in human resources departments is that the application of electronic systems requires high financial support. The study recommends, Interest in employing a human resource who has the skills and knowledge related to their mastery of technical systems, and making them within the criteria for passing job acceptance, and encouraging the culture of using information systems and workers to move from traditional management to electronic management, by providing financial and non-financial l incentives to employees who use less paper transactions through periodically monitoring and recording the number of records and works that are done in an automated manner.